The Golden Goose and Other Stories - Retod by Foulds, David (Oxford Oxford University Press, 2005)
Three brothers go to cut wood. The two older brothers come home with nothing, but the youngest one, Dummling, has a day of surprises. A friend gives him a bird with golden feathers. The golden goose leads Dummling through many adventures, until he finds a beautiful but serious princess, who never smiles or laughs. How does Dummling make her laugh?
Include Color Illustration
Keywords: Fairy tales -- Tales -- Folklore